2019
DOI: 10.3892/etm.2019.7475
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression and mutation of the RBPJ gene may be involved in CD59‑ clonal proliferation in paroxysmal nocturnal hemoglobinuria

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired clonal proliferative disease of hematopoietic stem cells. Various gene mutations, including the phosphatidylinositol glycan anchor biosynthesis class A (PIG-A) gene, may contribute to the proliferation of PNH clones. In order to explore the mechanism of PNH clone proliferation, a study was performed on 13 patients with PNH who underwent whole exome sequencing. The frequency of mutations in these patients was explored, and an additional 30 patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The differences between the patient and PNH mice models also reconfirmed that the proliferation advantage of PNH clones requires the participation of other unknown factors besides the PIG-A mutation. Some scholars have studied the secondary mutation genes of PNH patients and screened out some high-frequency mutations [ 29 31 ], while the mechanism research is still very difficult. The CKO heterozygous mice might be the suitable model for the further study.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the patient and PNH mice models also reconfirmed that the proliferation advantage of PNH clones requires the participation of other unknown factors besides the PIG-A mutation. Some scholars have studied the secondary mutation genes of PNH patients and screened out some high-frequency mutations [ 29 31 ], while the mechanism research is still very difficult. The CKO heterozygous mice might be the suitable model for the further study.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of secondary genetic mutations has been reported since the 1970s 21 . Additional mutant genes such as HMGA2 29 30 , WT1 31 , TET2 32 and RBPJ 33 have been reported in PNH patients. Most cases of PNH can carry additional mutations and these mutations are secondary strikes.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 , 24 Our previous research demonstrated that abnormal expression and mutation of RBPJ gene might contribute to CD59 − clonal proliferation. 25 In addition, a study from Byrne et al indicated that PIG‐A assay is a sensitive method for serial assessment of genomic instability in mouse models of MDS. 26 Therefore, whether PIG‐A gene mutation has resulted in the lack of CD59 deficiency in AML remains unclear.…”
Section: Discussionmentioning
confidence: 99%